The Role of Market Traders in Waste Management in the Lipa Market Environment, Teluk Mutiara District, Alor Regency - Arva Juniyati Putri Idris; Hamza H. Wulakada; Muhammad Husen Hasan (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Waste management in traditional markets remains a significant challenge in many regions, contributing to environmental degradation and public health concerns. This study aims to determine the potential for waste generation, the waste management system, and the role of traders in waste management in the Lipa Market environment, Teluk Mutiara District, Alor Regency. The method used is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the potential for waste generation in Lipa Market is very high, with inorganic waste being the dominant type. Waste management is not optimal due to limited facilities such as trash bins, low trader awareness regarding waste sorting, and an inefficient waste collection system. The role of traders in waste management is still minimal, as shown by their low participation in sorting, disposing of, and maintaining the cleanliness of the market environment. Therefore, it is recommended that relevant authorities enhance infrastructure, provide regular education and awareness programs, and involve traders more actively to establish a clean and sustainable market environment.